Pressure-induced redox reversal of iron and the distribution of elements in deep Earth - Xiaoli Wang; Xiaolei Feng; Jianfu Li; Yang Lv; Austin Ellis; Samantha Scott; Abhiyan Pandit; Dalar Khodagholian; Russell J. Hemley; Matthew G. Jackson; Frank Spera; Simon A. T. Redfern; et al. (Proceedings of the National Academy of Sciences, 2025)
We demonstrate a remarkable change in the chemical bonding of iron under pressure that underlies the distribution of elements in the Earth’s mantle and core. Using a massive-scale, first-principles study, we show that while reacting with p -block elements under increasing pressure from ambient to Earth core conditions, iron tends to reverse its redox nature, changing from an electron donor (reductant) to an electron acceptor (oxidant), and oxidizes many p -block elements. Such reverse redox propensity significantly impacts the stoichiometries, bond types and strengths, structures, and properties of iron compounds under deep planetary conditions. This change transforms many p- block elements (conventionally labeled lithophile or chalcophile) into highly siderophile species. The chemical binding strengths with iron show an inverse correlation with the depletion of p -block elements in the silicate Earth. Furthermore, silicon shows a distinct anomaly in its bonding to iron, which suggests silicon may readily be incorporated into Earth’s core.